2004
DOI: 10.1111/j.1365-246x.2004.02475.x
|View full text |Cite
|
Sign up to set email alerts
|

Onset of small-scale instabilities at the base of the lithosphere: scaling laws and role of pre-existing lithospheric structures

Abstract: S U M M A R YNumerical simulations of 2-D Rayleigh-Bénard convection are designed to study the development of convection at the base of the cooling lithosphere. A zero temperature is suddenly imposed at the mantle surface, which has initially a homogeneous temperature. The strongly temperature-dependent viscosity fluid is heated from within, in order to balance the internal temperature drift resulting from global fluid cooling. For a while, the lithosphere cools approximatively as a conductive half-space and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 27 publications
(81 reference statements)
6
49
0
Order By: Relevance
“…It has been shown that the effective viscosity at the lithosphere base, corresponding to a minimum if T -and P -dependences are both modelled, is crucial in triggering of small-scale convective processes (e.g. Davaille and Jaupart, 1993;Dumoulin et al, 2001;Morency et al, 2002;Dumoulin et al, 2005), as well as in subduction initiation, as it favours, if low enough, the corner flow activation necessary to stop the kinematic decoupling and mechanical coupling between the two converging plates at high depths (e.g. Doin…”
Section: Choice Of Rheological Parameter Setsmentioning
confidence: 99%
“…It has been shown that the effective viscosity at the lithosphere base, corresponding to a minimum if T -and P -dependences are both modelled, is crucial in triggering of small-scale convective processes (e.g. Davaille and Jaupart, 1993;Dumoulin et al, 2001;Morency et al, 2002;Dumoulin et al, 2005), as well as in subduction initiation, as it favours, if low enough, the corner flow activation necessary to stop the kinematic decoupling and mechanical coupling between the two converging plates at high depths (e.g. Doin…”
Section: Choice Of Rheological Parameter Setsmentioning
confidence: 99%
“…Initially convection is weak and the conductive geotherm in (6) is a good approximation of the actual geotherm. The thickness of the rheological boundary layer is proportional to the lithosphere thickness, which increases with the square root of age [64].…”
Section: Transient Heat Flow Through Oceanic Lithospherementioning
confidence: 99%
“…Sleep [17] gave calibrated relationships based on (17) for this situation. For comparison, Dumoulin et al [64,66] consider the time of convection to become vigorous which is analogous to t s using Rayeligh numbers. Their work utilizes t s , but their equations cannot be manipulated into the forms of (34) and (35).…”
Section: The Transient Heat Flow Equation (17) Then Becomes In Normalmentioning
confidence: 99%
See 2 more Smart Citations